2019
DOI: 10.3390/ijtpp4030030
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional CFD Simulation and Experimental Assessment of the Performance of a H-Shape Vertical-Axis Wind Turbine at Design and Off-Design Conditions

Abstract: The paper presents the results of a computational study on the aerodynamics and the performance of a small-scale Vertical-Axis Wind Turbine (VAWT) for distributed micro-generation. The complexity of VAWT aerodynamics, which are inherently unsteady and three-dimensional, makes high-fidelity flow models extremely demanding in terms of computational cost, limiting the analysis to mainly 2D or 2.5D Computational Fluid-Dynamics (CFD) approaches. This paper discusses how a proper setting of the computational model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Li et al (2013) achieved one of the first incompressible large eddy simulations (LES) on a limited span (what they called 2.5D) of a 3-NACA0015 blade H-Darrieus VAWT including the mast, at one single operating condition close to maximum efficiency. When compared to uRANS it improved performance predictions confirming results in Franchina et al (2019), and showed more turbulent structures shed by the blades at an operating condition close to maximum efficiency. However, the short span simulation may have triggered too coherent turbulent structures and both grid and numerical schemes too dissipative to yield any significant interaction between the blades and the mast.…”
Section: Introductionsupporting
confidence: 57%
“…Li et al (2013) achieved one of the first incompressible large eddy simulations (LES) on a limited span (what they called 2.5D) of a 3-NACA0015 blade H-Darrieus VAWT including the mast, at one single operating condition close to maximum efficiency. When compared to uRANS it improved performance predictions confirming results in Franchina et al (2019), and showed more turbulent structures shed by the blades at an operating condition close to maximum efficiency. However, the short span simulation may have triggered too coherent turbulent structures and both grid and numerical schemes too dissipative to yield any significant interaction between the blades and the mast.…”
Section: Introductionsupporting
confidence: 57%
“…Seeing that the details of numerical set-up and numerous obtained results can be found in [27], only a short summary is given here. Other extremely useful examples of flow simulations around VAWTs can be found in [28][29][30][31][32][33][34].…”
Section: Flow Simulationmentioning
confidence: 99%
“…the relative extents of the rotational and stationary parts of computational domain, mesh features and its level of medium fineness, material properties, zone and boundary conditions, adopted turbulence model, numerical schemes, etc. ), the complete modeling, meshing and computing processes were repeated on a VAWT of comparable dimensions, rotor solidity and employed airfoil (of slightly greater relative thickness) whose description and experimentally obtained data in a wind tunnel are available in [34,35]. The only difference is in the smaller turbulence intensity of 1% assumed along the inlet boundary (corresponding to the flow conditions in the wind tunnel).…”
Section: Flow Simulationmentioning
confidence: 99%
“…However, this article proposes an involute-type rotor blade in the VAWT model, because it supports the lift force as well as lift supporting drag force through an available conical-shaped space. Furthermore, the proposed involute-type blades with a wind accelerator, termed the wind flow modifier (WFM), are also adapted for simulation using 3D CFD ANSYS Fluent software [25][26][27] for the effective and reliable outcomes. The core objectives of this article are as follows:…”
Section: Introductionmentioning
confidence: 99%